The Dynamics of Coffee Shops as Creative Tourism Destinations in Enhancing Tourism Mataram City - Afwan Abrory (Digital Innovation : International Journal of Management, 2025)
This study explores the dynamics of Coffee Shops in fostering creative tourism in Mataram City, focusing on their role as a bridge between urban lifestyle experiences and local cultural promotion. As a relatively new phenomenon, coffee tourism remains an underdeveloped academic subject, with limited primary data available to understand its potential opportunities. The purpose of this research is to address these gaps by examining how Coffee Shops contribute to creative tourism, local economic development, and cultural preservation. Employing qualitative methods, including interviews, observations, and documentation, the study identifies key strategies and challenges faced by Coffee Shops in Mataram. Findings reveal that Coffee Shops not only enhance urban tourism experiences but also act as platforms for promoting local coffee products and cultural narratives. However, challenges such as supply chain instability, fragmented institutional policies, and limited integration with formal tourism sectors hinder their full potential. This research contributes to the growing body of literature on coffee tourism by providing insights into its role in sustainable urban tourism development and offering recommendations for policymakers and stakeholders.